Detection of carbapenemase activity in Enterobacteriaceae using LC-MS/MS in comparison with the neo-rapid CARB kit using direct visual assessment and colorimetry - Huber, Charlotte A.; Sidjabat, Hanna E.; Zowawi, Hosam M.; Kvaskoff, David; Reed, Sarah; McNamara, John F.; McCarthy, Kate L.; Harris, Patrick; Toh, Benjamin; Wailan, Alexander M.; Paterson, David L. (Journal of microbiological methods, 2016)
It has been described that the sensitivity of the Carba NP test may be low in the case of OXA-48-like carbapenamases and mass spectrometry based methods as well as a colorimetry based method have been described as alternatives. We evaluated 84 Enterobacteriaceae isolates including 31 OXA-48-like producing isolates and 13 isolates that produced either an imipenemase (IMP; n=8), New Delhi metallo-β-lactamase (NDM; n=3), or Klebsiella pneumoniae carbapenemase (KPC; n=2), as well as 40 carbapenemase negative Enterobacteriaceae isolates. We used the Neo-Rapid CARB kit, assessing the results with the unaided eye and compared it with a colorimetric approach. Furthermore, we incubated the isolates in growth media with meropenem and measured the remaining meropenem after one and 2h of incubation, respectively, using liquid chromatography tandem mass spectrometry (LC-MS/MS). Whilst all carbapenemase producing isolates with the exception of the OXA-244 producer tested positive for both the Neo-rapid CARB test using the unaided eye or colorimetry, and the 13 isolates producing either IMP, NDM or KPC hydrolysed the meropenem in the media almost completely after 2h of incubation, the 31 OXA-48-like producing isolates exhibited very variable hydrolytic activity when incubated in growth media with meropenem. In our study, the Neo-Rapid CARB test yielded a sensitivity of 98% for both the traditional and the colorimetric approach with a specificity of 95% and 100% respectively. Our results indicate that the Neo-Rapid CARB test may have use for the detection of OXA-48 type carbapenemases and that it may be particularly important to ensure bacterial lysis for the detection of these weaker hydrolysers.